MENAKAR BUDAYA LITERASI DI PESANTREN; Siginifikansi dan Relevansi Metode Programme for International Student Assessment - AR, Zaini Tamin; Kusaeri, Kusaeri; Alfiyah, Hanik Yuni; Purnamasari, Nia Indah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2021)
Most research on literacy focuses on formal educational institutions such as schools or higher education. There are not many studies that discuss literacy culture in pesantren. And so far, there are still no studies that discuss the evaluation of literacy culture in pesantren using the Program for International Student Assessment (PISA). Therefore, this study aims to analyze the significance and relevance of the PISA method as a means of assessing literacy culture in pesantren. Through literature study - with relevant current sources - this research finds that literacy culture in pesantren has taken root in the history of the spread of Islam in Indonesia. However, this is rarely studied because the term literacy is often identified with education in general educational institutions. In order to assess the level of literacy culture in pesantren, the PISA method is the most comprehensive and rigorous for assessing performance, translating, sampling and collecting data on santri, family, and institutional factors that can help explain differences in their performance and literacy skills. The author argues that PISA has relevance for assessing literacy culture in pesantren. In this case, the domain of reading literacy in PISA can be used as an instrument for cultural assessment of iqra', hifdz, bandongan, sorogan, mushawarah, muthala'ah, bahtsul masail and so on. This research can be used as an affirmation that there is a strong literacy culture in pesantren that has often gone unnoticed.